AB0629 Oral Glucocorticoids (GC) in Systemic Sclerosis (SSC): the Patient's Beliefs and Treatment Adherence. (10th June 2014) - Iudici, M.; Russo, B.; Mitidieri, M.; Cuomo, G.; Valentini, G.
Abstract : Background: Despite the lack of evidences supporting GC use in SSc and the potential risk to trigger a scleroderma renal crisis (1), these drugs are widely used in SSc patients (2). Knowing patients preferences and the beliefs they hold on a specific therapy is essential to drive the choice of clinicians and guidelines panelists, and to investigate the reasons of poor treatment adherence, which represent one hurdle to the achievement of the therapeutical goal. At the best of our knowledge, no study has been so far devoted to address SSc patient point of view about oral GC therapy. Objectives: To investigate how chronic GC intake is perceived by SSc patients in terms of necessity and concerns and if such beliefs can influence treatment adherence. Methods: Ninety-two SSc patients fulfilling the 2013 ACR/EULAR criteria, consecutively admitted to the Rheumatology Unit of the Second University of Naples were enrolled if they had been taking oral GC for >3 months prior to the visit. All patients underwent a complete clinical evaluation, laboratory investigations and were asked to complete 4 self-adminestered questionnaires namely the Beliefs about Medicines Questionnaire (Specific-BMQ), the 4-item Morisky medication adherence scale (MMAS-4), the Short-Form 36 (SF-36) and the Health Assessment Questionnaire Disability Index (HAQ-DI). Results: Seventy-seven out of 92 patients (83.6%) believed in the necessity of GC for maintaining health. Nevertheless, the majority of patients (67/92; 72.8%) reported concerns about potential adverse consequences i.e. the long-term effects of taking GC in 75 (81.5%) and the risk to become dependent on them in 53 patients (57.6%). In about half of patients (44 out of 92; 47.8%) their necessity score was lower than their concerns score (i.e. a negative necessity–concerns differential). Most of SSc patients (71.7%) were labeled as ambivalent (i.e. perceiving high necessity and high concern); a lower percentage (18.4%) as accepting (high necessity and low concern). In only 59 of 92 (64.1%) patients an high adherence rate (i.e. a MMAS-4 score of 0) was recorded. In univariate analysis, the necessity-concern differential was found to be correlated with the disease duration (ρ =0.205; p=0.049), treatment adherence (ρ =0.373; p=0.0002), mental component score (MCS) (ρ =0.324; p=0.01), duration of GC therapy (ρ =0.270; p=0.0009) and erythrocyte sedimentation rate (ρ =0.312; p=0.006). Stepwise multiple regression analysis showed that higher reported adherence (β=0.238;p=0.02) and disease duration (β=0.227;p=0.02) were associated with higher necessity-concern differential score. Conclusions: GC are perceived as necessary in the majority of SSc patients, but high concern about chronic (i.e.>3 months) GC use has emerged. Treatment adherence is not optimal. Given the high rate of patients worried about GC and the lack of studies driving their use, patient's preferences have to be taken into account and a shared decision with an informed patient is warranted in order to maximize patient's health. References: Steen V et al. Arthritis Rheum; 1998;41:1613-9 Iudici M et al. Clin Rheum 2014;33:153-64 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4665